2012
DOI: 10.1088/0256-307x/29/11/118101
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Optical Behavior of Germanium Quantum Dots

Abstract: Controlled growth, synthesis, and characterization of a high density and large-scale Ge nanostructure by an easy fabrication method are key issues for optoelectronic devices. Ge quantum dots (QDs) having a density of ∼10 11 cm −2 and a size as small as ∼8 nm are grown by radio frequency magnetron sputtering on Si (100) substrates under different heat treatments. The annealing temperature dependent structural and optical properties are measured using AFM, XRD, FESEM, EDX, photoluminescence (PL) and Raman spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…The growth mechanisms will be discussed in detail as a function of the RFMS parameters in a forthcoming paper where it will be shown that the QDs adopt dome-shaped structures similar to the ones reported by Samavati et al for germanium quantum dots [18] as depicted in Fig. S1.…”
Section: Afm Measurementsmentioning
confidence: 53%
See 1 more Smart Citation
“…The growth mechanisms will be discussed in detail as a function of the RFMS parameters in a forthcoming paper where it will be shown that the QDs adopt dome-shaped structures similar to the ones reported by Samavati et al for germanium quantum dots [18] as depicted in Fig. S1.…”
Section: Afm Measurementsmentioning
confidence: 53%
“…Controlling the sputtering parameters, such as the pressure in the vacuum chamber, also allows the tuning of the NPs size and therefore of their optical properties [13]. RFMS was previously successfully used for the deposition of TiO 2 , Ge, Si, ZnO, GaAs, CuInSe 2 and CdS QDs [13][14][15][16][17][18][19][20][21][22]. RFMS was also applied to the deposition of CdSe thin film and CdSe quantum dots embedded in SiO 2 or in an organic matrix [23,24].…”
mentioning
confidence: 99%
“…Several methods are employed to fabricate GIs with dierent sizes, such as chemical vapor deposition [1,2], radio frequency magnetron sputtering [3,4], molecular beam epitaxy [57], and thermal evaporation [8]. However, establishing a method to achieve suciently uniform island sizes with regular spatial distribution remains a critical issue.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the growth of Ge nanoislands using the Stranski-Krastanov mechanism is topically important and fundamentally challenging for device functionality. [1] Transforming an indirect band gap material (such as bulk Ge) to a direct gap material (nanosized Ge) gives rise to light emission, which is very attractive for full-color display as well as integrated optoelectronics technology. Among the techniques used to fabricate lowdimensional semiconductor structures, radio-frequency (rf) magnetron sputtering has several advantages, including low deposition temperature, higher film purity when compared to existing melting techniques, [2,3] easy fabrication, and low cost.…”
Section: Introductionmentioning
confidence: 99%